Identifikasi Kejadian Kecelakaan Kapal Berbasis Analisis Faktor Cuaca dan Citra Satelit (Studi Kasus Tanggal 18 Juni 2018 di Danau Toba) - Diana Cahaya Siregar; Sulton Kharisma; Bagas Ega Amirul Haq; Regina Dara Ninggar (Jurnal Fisika Indonesia, 2019)
KM Sinar Bangun IV was carrying passengers about 188 people and 70 units of vehicles when it sank in Lake Toba, North Sumatra on Monday, June 18, 2018. The incident was occurred due to overcapacity, bad weather condition, and human error. Meteorological analysis on a global, regional and local scales were used to determine atmospheric dynamics at the time of the event. Meanwhile, Satellite, AWS, and ARG data were used to determine the weather condition. Streamline analysis showed the shear line pattern in Sumatra Island and convergence in North Sumatra. The condition of sea surface temperature was warm enough in the range of 28-30 °C. These conditions triggered for the potential of convective clouds development. Himawari-8 satellite images from IR and VIS channels showed the development of convective clouds in Lake Toba right before the event happened. AWS and ARG measurements around the Lake Toba area recorded precipitation which the value was greater than 30 mm/day.